2014
DOI: 10.1037/a0031728
|View full text |Cite
|
Sign up to set email alerts
|

Situational context moderates the relationship between moral disengagement and aggression.

Abstract: Objective: In this study, we examined whether dispositional moral disengagement is associated with a specific act of laboratory-based aggression. No study, to our knowledge, has yet demonstrated this simple, yet necessary, link. We also investigated whether situational context moderated this relationship. Method: A university sample of 181 participants completed the Moral Disengagement Scale and the Hot Sauce Paradigm in an experimental design. Participants allocated hot sauce for consumption by a fictional pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…As a theoretical construct, moral disengagement has been measured and tested across diverse behavioral contexts. For example, it is a positive predictor of juvenile offending (Shulman, Cauffman, Piquero, & Fagan, 2011) aggression and delinquency (Bandura et al, 1996;Caprara et al, 2014;Pelton, Gound, Forehand, & Brody, 2004;White-Ajmani & Bursik, 2014), corporate crime (e.g., Bandura, Caprara, & Zsolnai, 2000;Detert, Sweitzer, & Trevino, 2008), dishonest academic behavior (e.g., Shu, Gino, & Bazerman, 2011), anti-social conduct in sport (e.g., Boardley & Kavussanu, 2007;Traclet, Moret, Ohl, & Clemence, 2015), and civic offenses such as vandalism (e.g., Caprara, Fida, Vecchione, Tramantano, & Barbaranelli, 2009). However, as previously stated, the construct of moral disengagement has received almost no empirical or theoretical application to the context of sexual violence.…”
mentioning
confidence: 99%
“…As a theoretical construct, moral disengagement has been measured and tested across diverse behavioral contexts. For example, it is a positive predictor of juvenile offending (Shulman, Cauffman, Piquero, & Fagan, 2011) aggression and delinquency (Bandura et al, 1996;Caprara et al, 2014;Pelton, Gound, Forehand, & Brody, 2004;White-Ajmani & Bursik, 2014), corporate crime (e.g., Bandura, Caprara, & Zsolnai, 2000;Detert, Sweitzer, & Trevino, 2008), dishonest academic behavior (e.g., Shu, Gino, & Bazerman, 2011), anti-social conduct in sport (e.g., Boardley & Kavussanu, 2007;Traclet, Moret, Ohl, & Clemence, 2015), and civic offenses such as vandalism (e.g., Caprara, Fida, Vecchione, Tramantano, & Barbaranelli, 2009). However, as previously stated, the construct of moral disengagement has received almost no empirical or theoretical application to the context of sexual violence.…”
mentioning
confidence: 99%
“…This assignment of exercises (which can cause discomfort) was the operationalization of aggression. This is similar to measures of aggression that involved delivery of unpleasant stimuli in a laboratory context such as allocating the amount of hot sauce that a target is to ingest (White-Ajmani & Bursik, 2014).…”
Section: Figurementioning
confidence: 94%
“…For example, Samnani et al found that the relationship between negative affect and counterproductive workplace behavior was stronger for those higher in dispositional moral disengagement [18]. White-Ajmani and Bursik found that after being insulted, individuals high in moral disengagement were more likely to harm the person who had insulted them (by making them drink hot sauce) [54]. And Panasiti and colleagues [55] found that moral disengagement did not trigger increased rates of lying an experimental game across the board, but individuals who were more morally disengaged were less affected by reputational risks when making a decision to lie.…”
Section: Moral Disengagement As a Moderatormentioning
confidence: 99%